Analisis Perencanaan Vaksinasi COVID-19 di RSUD Dr. H. Ibnu Sutowo Baturaja Tahun 2021 - Dhaneswari; Chairil Zaman (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Vaccination is an intervention that is considered effective to break the chain of Coronavirus Disease 2019 (COVID-19) transmission. In an effort to achieve high and equitable vaccination coverage, comprehensive planning is needed. This qualitative study aims to determine the general description of the COVID-19 vaccination planning at Dr. RSUD. H. Ibnu Sutowo Baturaja in 2021. Methods of data collection through in-depth interviews with 5 informants taken by purposive sampling that are Head of Medical Services, coordinator of vaccination, registration officer, screening officer, and vaccine giver vaccinator supported by observation and documentation. Data were analyzed including data reduction, data presentation, and verification. Planning for COVID-19 vaccination includes data collection of targets, establishment of health facilities, registration and verification of targets, calculation of vaccine needs and distribution and other logistics, preparation of advocacy plans, socialization, training, preparation of funding plans, and preparation of evaluation monitoring plans. The results showed that the vaccination targets were appropriate for each stage. Officer qualifications are appropriate. The schedule is in accordance with the target capacity and the principles of health protocols. Cold chain equipment inventory has been carried out previously. Targets can register either through the integrated application or by coming in person. Vaccine quantity planning and logistics have been in accordance with the target number and are provided by the Health Office. Limitations in logistics are complemented by hospital supplies. Advocacy, outreach and training have been planned. The hospital has not budgeted for COVID-19 vaccination activities, so it uses other fund allocations. In addition, there is no systematic evaluation monitoring plan. The hospital has carried out COVID-19 vaccination activities although there are still some although there are still some limitations